Pengaruh TPB dan Religiusitas Terhadap Minat Mahasiswa Berinvestasi di Pasar Modal Syariah : Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar - Bunayya, Ahmad Mahdi; Yunus, Ayu Ruqayyah; Sofyan, A. Syathir (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The enthusiasm of the millennial generation, as well as the simplicity with which the general public can acquire access to the capital market, are driving the expansion in total capital market participants. However, according to an additional study published by the BPS or the Central Statistics Agency in 2010, Indonesia had a population of about 237 million people. In comparison to the entire number of investors now present, the capital market business remains uninterested. This study investigates the impact of planned behavior theory and religiosity on student interest in participating in the Islamic capital market. The students of the Faculty of Islamic Economics and Business (FEBI) at UIN Alauddin Makassar are the subjects of this study. The students of FEBI UIN Alauddin Makassar who are interested in and have entered the realm of investment and have transacted in the Islamic capital market were chosen for this sample. The Structural Equation Model Partial Least Squares (SEM-PLS) method was used to examine the impact of attitude, subjective norm, behavioral control, and religion on student investment interest. According to the findings of this study, attitudes do not affect investment interest. However, this study backs up prior findings that there is a strong influence of subjective norm variables, behavioral control, and religion on investment interest. Keywords: Investment Interest; Islamic Capital Market; Religiosity; Theory of Planned Behavior